The Association of Vitamin D Levels with Monocyte-to-Lymphocyte-Ratio in Pulmonary Tuberculosis Patients - Nugraha, Kadek Nandita; Ajmala, Indana Eva; Dirja, Bayu Tirta; Andari, Marie Yuni (Jurnal Biologi Tropis, 2024)
One of the conditions associated with pulmonary tuberculosis (TB) is low vitamin D levels. Vitamin D has a role in stimulating antimicrobial peptides in various immune cells to create optimal immune function. Immune function is closely related to pulmonary TB pathophysiology, especially hematology changes. This makes the monocyte-lymphocyte ratio (MLR) a novel, affordable, and easy-to-perform inflammatory marker in pulmonary TB disease. This study aimed to determine whether there is a relationship between vitamin D levels and monocyte-lymphocyte ratio in patients with pulmonary tuberculosis at West Nusa Tenggara Provincial Hospital. This study was cross- sectional. The study subjects were all pulmonary TB patients in the period 2023-2024 in the inpatient installation who met the inclusion and exclusion criteria. Statistical analysis was performed using the Spearman rho correlation test. There were 43 samples in total, the majority of which were male (53.5%), in the productive age range of 18-64 years (74.4%), and body mass index in the underweight category (46.5%). The status category of vitamin D levels in patients was divided into deficiency (<20 ng/mL) (69.8%), insufficiency (21- 29 ng/mL) (20.9%), normal (30-100 ng/mL) (9.3%), and toxicity (>100 ng/mL) (0%). The monocyte-lymphocyte ratio (MLR) level from the patient's blood test results obtained a median of 0.66 with a minimum-maximum of 0.15-6.09. The results of statistical analysis obtained a p-value of >0.05. There is no significant relationship between vitamin D levels and monocyte-lymphocyte ratio in pulmonary tuberculosis patients at West Nusa Tenggara Provincial Hospital.